Investigation of the Stress Strain State of the Layer with a Longitudinal Cylindrical Thick-Walled Tube and the Displacements Given at the Boundaries of the Layer - Miroshnikov, V.Yu. (Проблеми машинобудування, 2019)
This paper proposes an analytical-numerical approach to solving the spatial prob-lem of the theory of elasticity for the layer with a circular cylindrical tube. The solution to the spatial problem of the theory of elasticity is obtained by the generalized Fourier method with respect to the system of Lamé's equations in the cylindrical coordinates associated with the tube and the Cartesian coordinates associated with the boundaries of the layer. Запропоновано аналітико-числовий підхід до розв’язання просторової задачі теорії пружності для шару з круговою циліндричною трубою. Розв’язок просторової задачі теорії пружності отримано узагальненим методом Фур’є стосовно системи рівнянь Ламе в циліндричних координатах, пов’язаних із трубою, та в декартових координатах, пов’язаних із межами шару. Предложен аналитико-численный подход к решению пространственной задачи теории упругости для слоя с круговой цилиндрической трубой. Решение пространственной задачи теории упругости получено обобщенным методом Фурье относительно системы уравнений Ламе в цилиндрических координатах, связанных с трубой, и декартовых координатах, связанных с границами слоя.